Culm and Leaf Epidermis of Indian Bamboos Part V- Gigantochloa Kurz Ex Munro - Agrawal, S. P.; Chauhan, Laxmi (Indian Forester, 1992)
Microscopic studies on epidermal features of culm and leaf of four species of Gigantochloa Kurz ex Munro have been described.